2021
DOI: 10.3390/ijms222111540
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ FTIR Study of DBD Plasma Parameters for Accelerated Germination of Arabidopsis thaliana Seeds

Abstract: Current agricultural practices are not sustainable; however, the non-thermal plasma treatment of seeds may be an eco-friendly alternative to alter macroscopic plant growth parameters. Despite numerous successful results of plasma-seed treatments reported in the literature, the plasma-treatment parameters required to improve plant growth remain elusive due to the plethora of physical, chemical, and biological variables. In this study, we investigate the optimal conditions in our surface dielectric barrier disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…Seeds were evaluated after 2−4 days in the filter paper or agar setup and after 7−9 days in perlite and soil setups. Unlike in several previous studies, 47,48,50,51 we did not observe a positive impact on germination on the filter paper and agar setups. This may be explained by a rather short treatment (1−300 s) in our setup versus over 900 s (15 min) in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Seeds were evaluated after 2−4 days in the filter paper or agar setup and after 7−9 days in perlite and soil setups. Unlike in several previous studies, 47,48,50,51 we did not observe a positive impact on germination on the filter paper and agar setups. This may be explained by a rather short treatment (1−300 s) in our setup versus over 900 s (15 min) in other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The study [80] revealed that treatment time and stress level are essential parameters that stimulate the germination of Arabidopsis thaliana seeds when exposed to DBD plasma. Prolonged treatment times and higher stress levels were found to accelerate the germination process.…”
Section: Dielectric Barrier Dischargementioning
confidence: 99%
“…Vertical farming, hydroponics, microorganisms, genetic engineering and also gas plasma agriculture are among those techniques. Gas plasma has recently received considerable attention for its application in sterilization and agriculture for its potential to enhance seed germination and healthy plant development (Bourke et al 2018 ; Weltmann et al 2019 ; Masiello et al 2021 ; Waskow et al 2021 ). Gas plasma is often called “the fourth state of matter,” along with solid, liquid and gas.…”
Section: Introductionmentioning
confidence: 99%